An introduction to global financial markets - Valdez, Stephen; Wood, Julian; Valdez, Stephen (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2003)
Providing comprehensive coverage of commercial and investment banking, foreign exchange, money and bond markets, trade finance, stock markets and other derivatives, this text is a primer for those who require a basic understanding or are new to the world of finance.
Banking 11 -- Securities Markets 105 -- Foreign Exchange and International Trade 197 -- Derivative Products 271 -- Insurance 329 -- The Periodic Global Crises 351 -- Trends in the Global Financial Markets 367.
'An extensively revised edition of An introduction to Western financial markets.'
Includes index.
Keywords: Finance; Finance -- Europe; Finance -- United States; Finance -- Japan; Financial institutions -- Europe; Financial institutions -- United States; Financial institutions -- Japan